von Willebrand factor interaction with the glycoprotein IIb/IIa complex. Its role in platelet function as demonstrated in patients with congenital afibrinogenemia. - De Marco, L (1986)
We have studied three afibrinogenemic patients, who had only trace amounts of plasma and platelet fibrinogen as measured by radioimmunoassay, and demonstrate here that the residual aggregation observed in their platelet-rich plasma is dependent upon von Willebrand factor (vWF) binding to the platelet membrane glycoprotein (GP)IIb/IIIa complex. The abnormality of aggregation was more pronounced when ADP, rather than thrombin, collagen, or the combination of ADP plus adrenaline was used to stimulate platelets. With all stimuli, nevertheless, the platelet response was completely inhibited by a monoclonal antibody (LJP5) that is known to block vWF, but not fibrinogen binding to GPIIb/IIIa. Addition of purified vWF to the afibrinogenemic plasma resulted in marked increase in the rate and extent of aggregation, particularly when platelets were stimulated with ADP. This response was also completely blocked by LJP5. Addition of fibrinogen, however, restored normal aggregation even in the presence of LJP5, a finding consistent with the knowledge that antibody LJP5 has no effect on platelet aggregation mediated by fibrinogen binding to GPIIb/IIIa. Two patients gave their informed consent to receiving infusion of 1-desamino-8-D-arginine vasopressin (DDAVP), a vasopressin analogue known to raise the vWF levels in plasma by two- to fourfold. The bleeding time, measured before and 45 min after infusion, shortened from greater than 24 min to 12 min and 50 s in one patient and from 16 min to 9 min and 30 s in the other. Concurrently, the rate and extent of ADP-induced platelet aggregation improved after DDAVP infusion. The pattern, however, reversed to baseline levels within 4 h. The concentration of plasma vWF increased after DDAVP infusion, but that of fibrinogen remained at trace levels. We conclude that vWF interaction with GPIIb/IIIa mediates platelet-platelet interaction and may play a role in primary hemostasis.